A cluster randomised controlled trial (cRCT) evaluation of a pre-driver education intervention using the Theory of Planned Behaviour. (April 2023) - Box, Elizabeth; Dorn, Lisa
Highlights: Worldwide, road traffic injuries are a leading cause of death amongst 5–29 year olds. Pre-driver education, commonly delivered to this at-risk group, is rarely effective. The intervention led to some small improvements in risk intentions, attitudes and other measures, which differed by sub-group. Practitioners are encouraged to design interventions with reference to behavioural science. Cluster randomised controlled trials are recommended for evaluation studies in the field of transport psychology. Abstract: Road traffic injuries are the leading of cause of death of 5–29-year-olds worldwide (World Health Organisation, 2018) making young driver safety a global public health concern. Pre-driver road safety education programmes are popular and commonly delivered with the aim of improving safety amongst this at risk group but have rarely been found to be effective (Kinnear, Lloyd, Helman, Husband, Scoons, Jones et al., 2013). A pre-driver education intervention (DriveFit) was designed and evaluated with a cluster randomised controlled trial (cRCT) using the Theory of Planned Behaviour (TPB) (Ajzen, 1991). The responses of 16–18-year-old students ( n = 437) from 22 schools/colleges in Devon, UK were analysed and showed that the DriveFit intervention led to some small improvements in risk intentions, attitudes, and other measures, which differed by sub-group. Speed intentions improved immediately post- intervention (T2), whereas a composite measure of all intentions and mobile phone use intentions improved at 8–10 weeks post-intervention (T3). Apart from speed intentions, a trend towards intentions becoming safer at T3 was noted. Mobile phone use and speeding attitudes, a composite measure of attitudes, as well as attitudes to driving violations and perceptions of risk, improved at T2 and T3, with the size of the effect slightly reduced at T3. Participants expressed safe views at baseline (T1), which overall left minimal room for improvement. Whilst previous research has found that education interventions deliver small self-reported effects, that diminish over time (i.e., Poulter and McKenna, 2010), this study finds small, but lasting attitude effects (which diminish in magnitude over time) and a trend towards improving intentions, over and above the control group. The findings provide some guidance on future research to design and evaluate educational interventions for pre- and novice drivers.